(untitled) (Research, Society and Development, 2022)
The investigation has a qualitative approach as a methodological procedure. The objective is to analyze the socioeconomic and environmental impacts of wind parks in the municipality of São José do Sabugi (PB), in the interior of Paraíba. As for the purposes, it consists of a descriptive research. As for the means, the research is characterized as bibliographical and documentary research. The municipality of São José do Sabugi-PB benefited from the collection of the Tax on Services of Any Nature (ISSQN). Income generation was mainly through land leases. Commercial activity was also affected, with the food sector being the most benefited. The forms of social participation took place through the work of the Environmental Protection Council (COPAM). The construction of roads was a positive point, but it became a problem, as vehicle traffic increased, generating the risk of accidents and changes in the daily lives of residents. During the road construction process there were impacts on the region’s flora. The generation of noise and alteration of the landscape are also impacts present during the operation of wind parks in the municipality. Positive impacts are perceived in relation to economic factors, such as the collection of taxes by the municipality and land leasing. Environmental impacts were also generated that need to be mitigated, as they put both the fauna and flora of the region at risk.